THE ROLE OF AUTHENTIC MATERIALS IN ENHANCING CULTURAL ADAPTABILITY IN FOREIGN LANGUAGE EDUCATION - Allayarova , Zebiniso; Jalilova, Nilufar (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This study explores the role of authentic materials in developing cultural adaptability in foreign language learning. Many learners struggle with real communication due to a lack of cultural awareness. This research analyzes the use of authentic resources such as videos and communication platforms like HelloTalk. The findings show that authentic materials improve learners’ understanding of cultural norms and enhance their communication skills. As a result, learners become more confident and effective in intercultural communication.